Chicken biodiversity and their management under backyard production system in Southern Rajasthan - SP Tailor; S Mishra; BL Dangi; Anand Jain (Journal of Livestock Biodiversity, 2025)
The characterization of chicken biodiversity of southern Rajasthan was undertaken through stratified random sampling survey of 300 poultry keepers from 60 villages in 12 tehsils of 6 districts. The information were collected on flock size, physical characteristics, egg production traits, egg characteristics, management practices and constraints in backyard poultry production system. All the surveyed farmers maintained coloured non-descript birds and followed backyard/free range system of rearing. The first choice was dual type in rural areas, closely followed by egg type in nearby cities. The native birds had mixed plumage colour, dull colour pattern, yellow skin and shank colour, red ear lobe, red single comb, and black eye. Average age at first egg production was 6.78±0.05 months and annual egg production was 43.16 ± 0.39 eggs. The average clutch size and pause period were 12.59 ± 0.13 and 107.05 ± 0.52 days, respectively. The number hatch brooding per year by a hen was 2.88 ± 0.08, while average chick hatched out per hatch was 9.52 ± 0.09. The average egg weight, length and breadth were 40.50±0.34 g, 4.75+0.02 cm and 3.47+0.01 cm, respectively. The average body weight in adult male and females were 1.91±0.02 and 1.25±0.04 kg. The average shank length in adult males and females were 8.35± 0.03 and 6.73±0.02 cm, respectively. The chickens were housed in katcha houses without proper bedding material. Predators posed major constraint for backyard poultry production in the region.